Leishmaniases of the New World: current concepts and implications for future research. - Grimaldi, G (1993)
Recent epidemiologic studies indicate that leishmaniasis in the Americas is far more abundant and of greater public health importance than was previously recognized. The disease in the New World is caused by a number of different parasite species that are capable of producing a wide variety of clinical manifestations. The outcome of leishmanial infection in humans is largely dependent on the immune responsiveness of the host and the virulence of the infecting parasite strain. This article reviews current concepts of the clinical forms, immunology, pathology, laboratory diagnosis, and treatment of the disease as well as aspects of its epidemiology and control. Recommendations for future research on the disease and its control are made.